Non-toxic materials for high efficiency thin-film solar cells: CZTSSe with In2S3 buffer layer - Yadav, Shweta; Chauhan, R. K.; Mishra, Rajan; Kumar, Saurabh (Indian journal of physics, 2024)
Thin-film solar cells based on Cu 2 ZnSn(S,Se) 4 (CZTSSe) are a promising technology for developing high-efficiency photo voltaic cells. These cells have excellent optical properties, a high absorption coefficient of over 10 4 cm −1 , and are made from abundant, non-toxic materials. The bandgap of CZTSSe can be adjusted between 1.0 to 1.5 eV. The objective of the present study was to investigate the performance of CZTSSe-based solar cells using In 2 S 3 and ZnSe buffer layers in place of the toxic CdS buffer layer. The study employed SCAPS software to simulate variations in the absorber and buffer layer thickness and doping concentration. As well as the effects of temperature, series/shunt resistance, and their impact on short-circuit current density, open-circuit voltage, fill factor, and efficiency on device performance are discussed. Results show that CZTSSe solar cells with In 2 S 3 as a buffer and MoS 2 as an HTL layer performed better, particularly at lower thicknesses. An 80-nm-thick In 2 S 3 buffer layer demonstrated the highest efficiency of 24.42%, compared to 23.55% for the ZnSe buffer layer. These findings suggest that In 2 S 3 is a promising alternative buffer layer for CZTSSe-based solar cells that can result in higher efficiency.